2021
DOI: 10.1101/2021.06.01.446610
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Intracerebral mechanisms explaining the impact of incidental feedback on mood state and risky choice

Abstract: Identifying factors whose fluctuations are associated with choice inconsistency is a major issue for rational decision theory. Here, we investigated the neuro-computational mechanisms through which mood fluctuations may bias human choice behavior. Intracerebral EEG data were collected in a large group of participants (n = 30), while they were performing interleaved quiz and choice tasks. Neural baseline activity preceding choice onset was confronted first to mood level, estimated by a computational model integ… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 53 publications
(81 reference statements)
0
3
0
Order By: Relevance
“…It is proposed that this internal affective information is integrated with external information to shape beliefs that rather than being objective, are motivated and biased by subjective feelings about the beliefs themselves, leading to a recursive influence of beliefs and affective states on each other 2,9,10 . Previous studies supported aspects of Bromberg-Martin and Sharot's framework 2 by demonstrating that internal beliefs and external feedback can elicit emotions like happiness, pride, or embarrassment [11][12][13][14][15][16][17] . Affective states also have been shown to alter decision making 13,18,19 and cognitive processes like situational judgments or learning styles 7 .…”
mentioning
confidence: 79%
“…It is proposed that this internal affective information is integrated with external information to shape beliefs that rather than being objective, are motivated and biased by subjective feelings about the beliefs themselves, leading to a recursive influence of beliefs and affective states on each other 2,9,10 . Previous studies supported aspects of Bromberg-Martin and Sharot's framework 2 by demonstrating that internal beliefs and external feedback can elicit emotions like happiness, pride, or embarrassment [11][12][13][14][15][16][17] . Affective states also have been shown to alter decision making 13,18,19 and cognitive processes like situational judgments or learning styles 7 .…”
mentioning
confidence: 79%
“…Similarly, beliefs are increasingly discussed as a cause and consequence of emotional states. In line with the "value of beliefs" framework (Bromberg- Martin & Sharot, 2020), studies demonstrate that internal beliefs and external feedback interact and thereby elicit emotions like happiness, pride, or embarrassment (Cecchi et al, 2022;Müller-Pinzler et al, 2015;Rutledge et al, 2016Rutledge et al, , 2014Stolz et al, 2020;Vinckier et al, 2019Vinckier et al, , 2018. Also, emotional states increase the probability of the presence of certain beliefs and shape belief-updating processes (Bromberg- Martin & Sharot, 2020;Müller-Pinzler et al, 2022).…”
Section: Emotional Statesmentioning
confidence: 89%

Self-belief formation

Krach,
Müller-Pinzler,
Czekalla
et al. 2024
Preprint
“…Whether any (and if so which) of these factors accounts for higher real-life mood changes in adolescence remains an open empirical question. Experimental and computational tools which have been developed over the last years [11,[13][14][15][16], combined with ecological momentary assessment in developmental populations, are available to elucidate these mechanisms further.…”
Section: Discussionmentioning
confidence: 99%
“…These theories emphasize that emotional states in health and psychopathology are affected by learning, and that emotional states, in turn, bias learning processes themselves. Recent studies in adults have revealed insight into the biological basis of such mood-learning dynamics using computational neuroimaging and neuropharmacological techniques [10][11][12][13][14][15][16][17][18][19]. Intriguingly, this also revealed implications of computational mood theories for real-world emotions outside of the lab [20,21].…”
Section: Moody Adolescents Through the Lens Of Algorithmsmentioning
confidence: 99%